Nestin in multiple myeloma: emerging insights into a potential therapeutic target - Yingmiao Wu; Yingmiao Wu; Ji Luo; Ji Luo; Yue Zhou; Yue Zhou; Jiaoya Lin; Yajie Wu; Yajie Wu; Shuai Zheng; Shuai Zheng; Jiao Chen; et al. (Frontiers in Oncology)
Multiple myeloma (MM) is the second most common hematological malignancy and remains incurable, with high rates of relapses and refractory. One of the root causes is the presence of multiple myeloma stem cells (MMSCs). The deficiency of MMSC treatment lies in the lack of specific targets. CD19, CD138, CD27, and ALDH have been regarded as markers for MMSCs; however, none of them can reliably identify MMSCs. Therefore, identifying unique markers of MMSCs is crucial. Nestin, a class-VI intermediate filament protein, was originally described as a marker of neuroepithelial stem/progenitor cells. Recently, nestin has been reported to be a useful marker and therapeutic target of cancer stem cell (CSC) in solid tumors, reflecting its importance in drug resistance and poor prognosis. Although nestin has been reported to be associated with poor prognosis in MM, its biological role in MM has not yet been thoroughly explored. This review summarizes the latest research progress of nestin in MM, including the characteristics of nestin, its role in CSCs across different cancers, the current status and cutting-edge detection technologies of MMSC, involved signaling pathways and clinical relevance in MM. It emphasizes that nestin is a more specific and effective potential therapeutic target for MMSC.